Dual Infection of an Open Fracture Caused by Mycobacterium setense and Clostridium celerecrescens - Ryskova, Lenka; Zahradnicek, Jan; Kukla, Rudolf; Bolehovska, Radka; Vajda, Milan; Pavlik, Ivo; Bostik, Pavel; Ryska, Pavel (Antibiotics (Basel, Switzerland), 2022)
Infections caused by Mycobacterium setense or Clostridium celerecrescens are extremely rare. In this report, for the first time a dual infection with these two pathogens is described. An 18-year-old female suffered multiple injuries, including an open comminuted fracture of the right humeral diaphysis after falling from a fifth-floor balcony in January 2019. Five months after the accident, a fistula appeared in the scar, reaching the bone tissue. M. setense and C. celerecrescens were cultured from sinus swabs and subsequently from perioperative samples. The patient was initially treated with a combination of intravenous antibiotics (ATBs): imipenem, amikacin, and ciprofloxacin. One month after the fracture fixation with a titanium nail, C. celerecrescens was again detected; therefore, metronidazole was added to the therapy. A triple combination of oral (PO) ATBs (trimethoprim-sulfamethoxazole, moxifloxacin, and metronidazole) followed, 8 weeks after the initial intravenous therapy. C. celerecrescens was cultured again two times, most recently in November 2019, when surgical debridement was supplemented by the topical administration of cancellous bone impregnated with vancomycin. Signs of bone healing were found at follow-ups and ATB treatment was finished in March 2020 after a total of 9 months of therapy. To this day, there have been no signs of reinfection. This case thus illustrates the need for a combination of systemic and individualized local therapy in the treatment of complicated cases of dual infections with rare pathogens.
Keywords: fracture-related infection; nontuberculous mycobacteria; post-traumatic osteomyelitis; rapidly growing mycobacteria